Telereabilitação para a dor no ombro: efetividade do tratamento e autoeficácia para exercícios domiciliares - Gava, Vander (2024)
Shoulder pain is a highly prevalent musculoskeletal condition that imposes significant limitations on individuals' functionality and quality of life. Telerehabilitation is an emerging intervention that leverages digital technologies to deliver physical therapy remotely, potentially overcoming accessibility barriers. Additionally, psychosocial factors such as self-efficacy play a critical role in adherence to rehabilitation programs, necessitating valid tools for their measurement. This thesis integrates a systematic review, a translation and validation study, and a randomized controlled trial to explore the effectiveness of telerehabilitation and its interaction with self-efficacy in individuals with shoulder pain. Study 1 Objective: To systematically review the effectiveness of telerehabilitation in improving pain and disability in individuals with shoulder pain. Methods: A systematic search of PubMed, Embase, CINAHL, LILACS, Cochrane. Randomized controlled trials investigating telerehabilitation’s effects on pain and disability in individuals with shoulder pain were included. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool, and the evidence level was graded using the GRADE approach. Results and Conclusion: Six randomized controlled trials with 368 participants were included. Low evidence suggested no difference between telerehabilitation and in-person physiotherapy or home-based exercise programs for pain and disability. Telerehabilitation was superior to advice-only interventions in improving pain (effect size: 2.42) and disability (effect size: 1.61). Despite its potential, the low quality of evidence underscores the need for further high-quality trials to support telerehabilitation’s routine use. Study 2 Objective: To translate, culturally adapt, and validate the Self-Efficacy for Home Exercise Programs Scale (SEHEPS) from English to Brazilian Portuguese in individuals with chronic shoulder pain. Methods: The SEHEPS was translated and culturally adapted following international guidelines. Psychometric properties, including reliability, construct validity, and responsiveness, were assessed in a sample of individuals with shoulder pain over a 12-week clinical trial. Construct validity was examined through correlations with the Chronic Pain Self-Efficacy Scale (CPSS) and the Exercise Adherence Rating Scale (EARS). Results and Conclusion: The Brazilian Portuguese SEHEPS demonstrated excellent reliability (ICC = 0.73) and internal consistency (α = 0.93). Construct validity was supported by moderate correlations with CPSS (ρ = 0.45) and EARS (ρ = 0.46). Responsiveness to clinical changes was confirmed over the intervention period. These findings validate the SEHEPS as a robust instrument for assessing self-efficacy in home exercise programs, with applications in clinical and research contexts. Study 3 Objective: To compare the effectiveness of telerehabilitation and in-person physiotherapy for treating individuals with chronic shoulder pain in a non-inferiority randomized controlled trial. Methods: A total of 184 participants were randomized into telerehabilitation or in-person physiotherapy groups. Both groups underwent a 12-week exercise program targeting scapulothoracic muscles. Primary outcomes included pain and disability, measured by the Shoulder Pain and Disability Index (SPADI). Secondary outcomes included self-efficacy, kinesiophobia, and satisfaction. Results and Conclusion: Telerehabilitation was not significantly different to in-person physiotherapy in improving SPADI scores (mean difference = -1.97; 95% CI: -9.10, 5.15) and comparable in reducing kinesiophobia and improving upper limb function. Non-inferiority remained inconclusive, however. Self-efficacy and satisfaction scores were higher in the in-person group. These results highlight telerehabilitation as a feasible and effective alternative, particularly for individuals with limited access to traditional care.